Examining academic performance across gender differently: Measurement invariance and latent mean differences using bias-corrected bootstrap confidence intervals - Tsaousis, Ioannis; Alghamdi, Mohammed H. (Frontiers in Psychology, 2022)
The aim of this study was threefold: first, to examine the dimensionality of the construct of General Academic Ability (GAA) at the subscale level providing additional insights over and above on the conceptualization of the construct as introduced and discussed by Dimitrov et al. (2015). Second, to explore different degrees of measurement invariance of the GAA across gender using more recent advancements in the examination of Measurement Invariance (i.e., Bias-Corrected bootstrap Confidence Intervals). Third, to examine gender differences across the different facets of the GAA at the latent mean level. The sample consisted of 1800 high school graduates who applied for higher education in Saudi Arabia. The results from the analysis indicated that the hierarchical model with one higher-order factor (i.e., general academic ability) and four lower-order cognitive factors (i.e., verbal ability, quantitative ability, scholastic aptitude, and GPA) exhibited an excellent fit to the data. In terms of the measurement invariance hypothesis, it was found that the hierarchical model exhibits full configural and metric invariance and partial scalar invariance. Finally, using the Latent Mean Difference procedure, the results showed gender differences in the Verbal and GPA domains. Although significant differences were also found in the Scholastic aptitude domain, this finding is not stable due to several non-invariant items within the domain. In both cases, females scored higher than males. Finally, regarding the higher-order factor (GAA), the results showed that females scored higher than males. There were no significant differences in the Quantitative domain.